Overall deformation of steel-concrete-steel immersed structures during construction stage considering temperature effect. (December 2022) - Wei, Xiao-Chen; Liu, Yu-Fei; Song, Shen-You; Fan, Jian-Sheng; Su, Zong-Xian
Abstract: Temperature effect is one of the most significant factors to be considered in large-scale structures. For steel–concrete-steel composite immersed structures, the overall deformation is a closely watched indicator in the construction process. The main aim of this study is to investigate the overall deformation of steel–concrete-steel composite immersed structures during the construction stage, and thus a new numerical method comprehensively considering the temperature effect and material properties of early-age concrete is proposed. In the proposed method, a new finite element program for composite immersed structures, including thermal and structural modules, is developed in ANSYS. Firstly, the time-varying temperature distribution of the structure during the construction stage is accurately simulated by a transient thermal analysis, allowing for concrete hydration, solar radiation, air temperature, and changes of thermal properties comprehensively. Secondly, based on the ANSYS User-Programmable Features (UPFs), the stress–strain constitutive law of the concrete is redefined by modifying the material subroutine to consider the hardening and shrinkage of early-age concrete, then the overall structural deformation during the construction stage is estimated in the case that accurate temperature distribution and material properties are fully considered. Finally, a full-scale model of the composite immersed tunnel in Shenzhong Link is taken as an application case. The accuracy of simulation results is verified with the data of on-site monitoring. The results show that the temperature field of the composite immersed structure is obviously non-uniform and time-varying, and the overall contraction in lateral and longitudinal directions happens after the construction due to the variation of temperature and behaviors of early-age concrete.